Coaches' perspectives about the act of mentoring within a sport coaching context - Mac Intosh, Andrew (ProQuest Dissertations & Theses, 2016)
Research on mentoring has been taking place for decades and has spanned many contexts. In spite of this work and the widely held belief that mentoring works, very little research related to the phenomenon of mentoring has taken place in the sport context. More specifically, while some studies have examined the role of mentoring in the development of future coaches, very little has explored how coaches might serve as mentors to their athletes. Given the number of youth within sport and the roles that coaches play in sport, there is evidence to suggest that coaches might play the role of mentor to their athletes. In the quest to learn more about how mentoring takes place in this context, this study interviewed 13 coaches (4 males, 9 females) who coached with a character based sport organization in inner city Detroit. All coaches described themselves as mentors to their athletes. They also described very close relationships with athletes demonstrating the extent to which mentoring is a part of what they do as coaches. Coaches described mentoring as being made up of different functions depending on context, providing benefits to mentor and mentee and having challenges. The structure of mentoring in sport however, may be a blend of formal and informal approaches considered thus far in the research. This is exciting as we begin to examine the potential that mentoring in sport might hold for holistic athlete development and the teaching of life skills.